In vivo Doppler Ultrasound Quantification of Turbulence Intensity Using A High-Pass Frequency Filter Method - Thorne, Meghan L.; Rankin, Richard N.; Steinman, David A.; Holdsworth, David W. (Ultrasound in medicine & biology, 2010)
The objective of this investigation was to implement a high-pass frequency filter method to analyze Doppler ultrasound velocity waveforms and quantify turbulence intensity (TI) in vivo. Doppler velocity data were analyzed using two techniques, based on either ensemble averaging or high-pass frequency domain filtering of the periodic waveforms. The accuracy and precision of TI measurements were determined with controlled in vitro experiments, using a pulsatile-flow model of a stenosed carotid bifurcation. The high-pass filter technique was also applied in vivo to determine whether this technique could successfully distinguish between pertinent hemodynamic sites within the carotid artery bifurcation. Twenty-five seconds of Doppler audio data were acquired at three sites (common carotid artery [CCA], internal carotid artery [ICA] stenosis and distal ICA) within 10 human carotid arteries, and repeated three times. Doppler velocity data were analyzed using a ninth-order high-pass Butterworth filter with a 12-Hz inflection point. TI measured within the CCA and distal ICA was found to be significantly different ( p < 0.0001) for moderate to nearly occluded carotid artery classifications. Also, TI measured within the distal ICA increased with stenosis severity, with the ability to distinguish between each stenosis class ( p < 0.05). This investigation demonstrated the ability to precisely quantify TI using a conventional Doppler ultrasound machine in human subjects, without interfering with normal clinical protocols. (E-mail: david.holdsworth@imaging.robarts.ca)